STP Position Paper: Recommended Practices for Sampling and Processing the Nervous System (Brain, Spinal Cord, Nerve, and Eye) during Nonclinical General Toxicity Studies. (October 2013) - Bolon, Brad; Garman, Robert H.; Pardo, Ingrid D.; Jensen, Karl; Sills, Robert C.; Roulois, Aude; Radovsky, Ann; Bradley, Alys; Andrews-Jones, Lydia; Butt, Mark; Gumprecht, Laura
The Society of Toxicologic Pathology charged a Nervous System Sampling Working Group with devising recommended practices to routinely screen the central nervous system (CNS) and peripheral nervous system (PNS) in Good Laboratory Practice–type nonclinical general toxicity studies. Brains should be weighed and trimmed similarly for all animals in a study. Certain structures should be sampled regularly: caudate/putamen, cerebellum, cerebral cortex, choroid plexus, eye (with optic nerve), hippocampus, hypothalamus, medulla oblongata, midbrain, nerve, olfactory bulb (rodents only), pons, spinal cord, and thalamus. Brain regions may be sampled bilaterally in rodents using 6 to 7 coronal sections, and unilaterally in nonrodents with 6 to 7 coronal hemisections. Spinal cord and nerves should be examined in transverse and longitudinal (or oblique) orientations. Most Working Group members considered immersion fixation in formalin (for CNS or PNS) or a solution containing acetic acid (for eye), paraffin embedding, and initial evaluation limited to hematoxylin and eosin (H&E)-stained sections to be acceptable for routine microscopic evaluation during general toxicity studies; other neurohistological methods may be undertaken if needed to better characterize H&E findings. Initial microscopic analyses should be qualitative and done with foreknowledge of treatments and doses (i.e., "unblinded"). The pathology report should clearly communicate structures that were assessed and methodological details. Since neuropathologic assessment is only one aspect of general toxicity studies, institutions should retain flexibility in customizing their sampling, processing, analytical, and reporting procedures as long as major neural targets are evaluated systematically.